Perspektif Kepuasan Penumpang Dalam Kualitas Pelayanan Kapal Feri: Studi Kasus Pelabuhan Penyeberangan Merak-Bakauheni - Rhaptyalyani Herno Della; Ashari Fitra Rachmannullah (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
This study evaluates passenger satisfaction from the perspective of service quality. The sample was collected by sending questionnaires from two perspectives; ferry passengers and ferry company employees at Merak-Bakauheni port in Indonesia. The PZB model is used for gap analysis and SERVQUAL dimension to assess and evaluate the service quality. The results show gaps between passenger satisfaction and ferry service quality at the Merak port - Bakauheni port. Data analysis using t-pairwise statistical method. The analysis found that gap 1; gap in perspective between the passenger expectations service and the ferry companies perceptions of their passengers expectation is very large, with the largest attributes from tangibles dimension. The largest gap of attributes from that dimension is “convenience store at the terminal.” In gap 5, the perceptions of passengers' expected and their perceived of service showed that the attribute of “Ferry service provides online services to facilitate customers” as the largest gap. Thus, from this study, ferry services need to make reformation, especially in the attribute that has a large gap. Moreover, this study provides an overview to ferry service in Indonesia to enhance their service quality.